Live–Postbiotic Multistrain Platform for Immune-Response Regulation and Barrier Restoration in Experimental Colitis - Ziraoui, Anas; Hollingsworth, Frederick; Foster, Dylan (International Journal of Public Health and Medical Research, 2026)
We evaluated a BALIMONT live–postbiotic multistrain platform centered on Lactobacillus acidophilus ATCC 4356, Lactobacillus plantarum DSM 20174, and Bifidobacterium longum DSM 20219 for immune-response regulation and attenuation of experimental colitis. The live fraction was balanced at a viable-count ratio of 2:3:5 and paired with homologous postbiotic fractions at a live-bacteria-to-postbiotic mass ratio of 1:2. In the preclinical dataset retained in this manuscript, three BALIMONT variants were compared with a live-bacteria-only formulation in a DSS-induced colitis model. Across the BALIMONT variants, total inflammatory-burden reduction reached 65.7%–68.2%, whereas the live-bacteria-only comparator achieved 32.5%; tight-junction protein upregulation reached 40.1%–42.6% versus 18.3%, respectively. To place these findings in clinical context, we reviewed published randomized and controlled human studies of probiotics, synbiotics, and related microbiota-directed therapies in ulcerative colitis. Human trials involving Bifidobacterium longum, Bifidobacterium breve, Lactobacillus acidophilus-containing combinations, and Escherichia coli Nissle 1917 have reported improvements in sigmoidoscopy or endoscopy, disease-activity indices, mucosal inflammatory signaling, or remission-related outcomes, although effect sizes were strongly formulation- and strain-dependent. Taken together, our retained preclinical results and the published clinical literature support the translational plausibility of a live–postbiotic strategy for immune modulation and barrier restoration, while also showing that exact-strain clinical confirmation remains necessary.